Особливості стратегічного планування та цільового програмування в оборонній сфері України - Сокуренко, В. В.; Sokurenko, V. V.; Valerii Sokurenko (Право і безпека. – 2017. – № 2 (65). – С. 54-64, 2017)
Розкрито зміст стратегічного планування у сфері оборони України та сформульовано перелік його основних завдань і принципів. Окреслено перелік елементів системи стратегічного планування та розкрито їх зміст. Охарактеризовано суб’єктів стратегічного планування у сфері оборони держави. З’ясовано зміст цільового програмування у цій сфері та визначено його мету. Запропоновано внести доповнення до національного адміністративного законодавства, що визначає особливості процесів стратегічного планування та цільового програмування, а також регулює діяльність органів публічної адміністрації у цій сфері.

It has been determined that strategic planning is the activity of competent subjects for the development and implementation of the main directions and plans of the public administration for forecasting, planning and programming of the state policy in the defense sector aimed at ensuring the national security and defense of the state. The list of the tasks of strategic planning has been formulated. The necessity of incorporating state enterprises, institutions and organizations into defense planning subjects has been grounded in order to harmonize the legislation in the defense sector by making appropriate amendments and alterations to the legislative acts regulating this issue. It has also been determined that elements of the strategic planning system are: 1) defense planning; 2) economic planning; 3) social planning; 4) military planning; 5) technical planning; 6) target programming. The content of each element of the strategic planning system has been revealed. The subjects of strategic planning are the competent public administration agencies that are empowered in the defense sector as part of the substantiation of the perspectives for the development of military command and other military formations taking into account the nature of actual and potential threats in the defense sector and economic capabilities of the state, with the indication of concrete measures, executors and the timing of their implementation in order to ensure the necessary level of state defense, the integrity of its borders and sovereignty. The definition of the concept of “principles of strategic planning” has been provided, and the author has offered to include the following principles: unity and integrity; separation of powers; continuity and continuity; balance of the strategic planning system; the effectiveness and efficiency of strategic planning; responsibility of the participants in strategic planning; transparency (openness) of strategic planning; realism; resource security; measurability of goals; matching metrics to goals; targeted programming; systematic and parallel of the process of strategic planning with the preservation of collegiality in decision-making; continuity of management of the strategic planning process; timeliness and adequacy of measures to protect Ukraine’s national interests from external and internal threats in the military sphere; state-guaranteed organizational, technical, methodological, informational, material and financial provision for the implementation of plans and state programs in the defense sector and ensuring their effective use. According to the author, targeted programming in the defense sector is a professional activity of the subjects of strategic planning for the development and implementation of state and municipal development programs of the state and ensuring its defense capability, which are contained in the strategic planning documents and are developed for a specifically defined purpose. It has been clarified that the purpose of targeted programming is: a) definition of strategic settings in the defense sector; b) substantiation of requirements in qualitative and quantitative composition of armament; c) the establishment of priorities for solving the problems of defense by software methods; d) rational allocation of resources into targeted integrated programs in accordance with established priorities; e) assessing the conformity of the results achieved with the objectives and implementation of, if necessary, adjusting the allocation of appropriations.

Раскрыто содержание стратегического планирования в сфере обороны Украины и сформулирован перечень его основных задач и принципов. Определен перечень элементов системы стратегического планирования и раскрыто их содержание. Охарактеризованы субъекты стратегического планирования в сфере обороны государства. Выяснено содержание целевого программирования в сфере обороны и определены его цели. Предложено внести дополнения к национальному административному законодательству, определяющему особенности процессов стратегического планирования и целевого программирования, а также регулирующему деятельность органов публичной администрации в этой сфере.
Features of strategic planning and targeted programming within the defense sector of Ukraine
Особенности стратегического планирования и целевого программирования в оборонной сфере Украины
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; стратегічне планування; цільове програмування; публічна адміністрація; державна політика; оборона країни; законодавство; гармонізація законодавства; органи військового управління; strategic planning; targeted programming; public administration; state policy; defense; legislation; harmonization; military management agencies; стратегическое планирование; целевое программирование; публичная администрация; государственная политика; оборона страны; законодательство; гармонизация законодательства; органы военного управления